Virtual Power Plant for Residential Demand Response - Rotger-Griful, Sergi (Technical Report Electronics and Computer Engineering, 2014)
This report presents the progress done in the first 1.5 years in relation to the PhD project “Virtual Power Plant for Residential Demand Response”. The PhD project aims to gain insight on demand response provision in residential buildings by using a Virtual Power Plant (VPP) in a smart grid scenario. The document shows an architectural overview of the designed VPP and a prototype of the latter based on industrial automation equipment. Furthermore, the report introduces the control strategy of the VPP. This strategy is based on a model predictive control approach to locally optimize energy resources and to provide demand response to an aggregator. In addition, an initial study on prediction models for electricity consumption of residential buildings is presented. Load forecasting models like the ones described are used by the intelligence of the VPP for decision making. The report concludes by outlining the future work together with the planed publications that will lead to timely completion of the PhD study.